Повести - Алексеев Валерий Алексеевич (Детская литература, 1989)
Экземпляры: ДБ; ф16 (20221024) / Инвентарный номер: 21232 / Цена: 1.30 / Сис.шифр: Р2ср / Авт.знак: А 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6